Educational level and tuberculosis mortality in Colombia: growing inequalities and stagnation in reduction - Salomé Valencia-Aguirre; Ivan Arroyave; Alberto L. García-Basteiro (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2022)
We aim to describe the role of educational inequalities, for sex and age groups, in adult tuberculosis (TB) mortality in Colombia, 1999-2017. We linked mortality data to data estimation of the national population based on censuses and surveys to obtain primary, secondary, and tertiary adult (25+ years of age) age-standardized mortality rates (ASMR) by educational level. Thus, a population-based study was conducted using national secondary mortality data between 1999 and 2017. Tuberculosis age-standardized mortality rates were calculated separately by educational level, sex, and age groups, using Poisson regression models. Educational relative inequalities in adult mortality were evaluated by calculating the rate ratio, and the relative index of inequality (RII). Trends and joinpoints were evaluated by annual percentage change (APC). We found that, out of the 19,720 TB deaths reported, 69% occurred in men, and 45% in older adults (men and women, aged 65+). Men presented higher TB mortality rates than women (ASMR men = 7.1/100,000 inhabitants, ASMR women = 2.7/100,000 inhabitants). As mortality was consistently higher in the lowest educational level for both sexes and all age groups, inequalities in TB mortality were found to be high (RII = 9.7 and 13.4 among men and women, respectively) and growing at an annual rate of 8% and 1%. High and increasing inequalities, regarding educational level, in TB mortality in Colombia suggest the need to comprehensively address strategies for reducing TB by considering social determinants and including health education strategies throughout the country.